Self-synchronized converter for fast synchronization between low voltage microgrid and inverter connection - Amin, Md Ruhul (2017)
In this research, a fast-synchronization between single-phase microgrid and inverter in low voltage, which is based on virtual synchronous converter (VSCon) technique is been developed. This technique does not require any phase locked loop (PLL) circuit as an external control structure for the synchronization of the inverter. As known, PLL is a common technique in order to synchronize the amplitude, phase-angle and frequency between a microgrid and an inverter in distributed generation network. Previous studies show that, the disadvantage of PLLs is where the non-linear characteristic on the signal process will result the inverter control to be non-linear. Therefore, it is difficult and lengthy process to tune the PLL gains to reach suitable performance in order to synchronize the voltage, phase-angle and frequency between microgrid and inverter. As a result, a VSCon is been developed in which it is a self-synchronized inverter which is based on synchronous generator mathematical model. This controller acts like as synchronous generator operating system in inverter control loop in order to achieve fast voltage, phase and frequency synchronization between inverter-microgrid connection. This technique has been modeled, simulated and tested in Matlab/Simulink software. It is by using a single-phase AC source input system connecting with several load variations during simulation period. This VSCon has been placed in inverter control loop to generate a pulse width modulation (PWM) signal that responds to the grid information for to synchronizing the inverter output voltage with the grid voltage. A single source input at 120V, 50Hz frequency and 240V, 50Hz frequency are used in order to see the self-synchronization response between a microgrid and an inverter. Furthermore, it also been tested when the grid frequency has been changed from the rated frequency at 50Hz to 51Hz and the result shows that, VSCon takes nearly 1-cycle to synchronize to this new frequency value. The grid phase angle test also has been conducted. For this test, the voltage grid which has 100 phase delay has been created in the input voltage source at microgrid side. As a result, the VSCon is also able to achieve self-synchronization with this new source